Protocol: An updated integrated methodology for analysis of metabolites and enzyme activities of ethylene biosynthesis - Geeraerd Annemie H; De Proft Maurice P; Hertog Maarten LATM; Van de Poel Bram; Bulens Inge; Nicolaï Bart M (Plant Methods, 2011)
Abstract Background The foundations for ethylene research were laid many years ago by researchers such as Lizada, Yang and Hoffman. Nowadays, most of the methods developed by them are still being used. Technological developments since then have led to small but significant improvements, contributing to a more efficient workflow. Despite this, many of these improvements have never been properly documented. Results This article provides an updated, integrated set of protocols suitable for the assembly of a complete picture of ethylene biosynthesis, including the measurement of ethylene itself. The original protocols for the metabolites 1-aminocyclopropane-1-carboxylic acid and 1-(malonylamino)cyclopropane-1-carboxylic acid have been updated and downscaled, while protocols to determine in vitro activities of the key enzymes 1-aminocyclopropane-1-carboxylate synthase and 1-aminocyclopropane-1-carboxylate oxidase have been optimised for efficiency, repeatability and accuracy. All the protocols described were optimised for apple fruit, but have been proven to be suitable for the analysis of tomato fruit as well. Conclusions This work collates an integrated set of detailed protocols for the measurement of components of the ethylene biosynthetic pathway, starting from well-established methods. These protocols have been optimised for smaller sample volumes, increased efficiency, repeatability and accuracy. The detailed protocol allows other scientists to rapidly implement these methods in their own laboratories in a consistent and efficient way.